Development and validation of the self-consciousness type scale - Lee, Jiye; Baek, Hyemi; Oh, Eunjee; Kim, Jin-young; Ko, Young-gun (Frontiers in Psychology, 2024)
Previous research has highlighted the duality of self-consciousness, simultaneously playing adaptive and maladaptive roles. The present study aims to develop a measure that categorically distinguishes between different types of self-consciousness style based on the Regulatory Focus Theory (RFT) and to examine their relationship with mental health related indicators. Data were gathered through an online mental health survey at a University Student Counseling Center in Seoul. Exploratory factor analysis, confirmatory factor analysis, reliability and validity analysis were conducted, resulting in the development of a 14-question Self-Consciousness Type Scale (SCTS). Both exploratory and confirmatory factor analyses validated the 2-factor structure. The fit indices of the final model indicated a good fit, with high internal consistencies for both sub-factors. Furthermore, convergent and discriminant validity were confirmed through correlations between the sub-scales. Consequently, cluster analysis identified four distinct subtypes of self-consciousness styles: Growth-oriented, Defensive, Ambivalent, and Low focus self-consciousness. Group difference analysis revealed that each subtype demonstrated significant differences in mental health-related variables, supporting the 2x2 model of prevention-focused and promotion-focused self-consciousness. The findings support the SCTS as a valid measurement tool capable of distinguishing four distinct types of selfconsciousness, aligning with the multidimensional model of self-consciousness. Based on the results, limitations, and implications of the study were discussed.